2011
DOI: 10.1007/978-1-61779-286-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Use of Formalin-Fixed and Paraffin-Embedded Tissues for Diagnosis and Therapy in Routine Clinical Settings

Abstract: Formalin-fixed and paraffin-embedded (FFPE) tissues are used routinely everyday in hospitals world-wide for histopathological diagnosis of diseases like cancer. Due to formalin-induced cross-linking of proteins, FFPE tissues present a particular challenge for proteomic analysis. Nevertheless, there has been recent progress for extraction-based protein analysis in these tissues. Novel tools developed in the last few years are urgently needed because precise protein biomarker quantification in clinical FFPE tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…It has been assumed that the cross-linking of proteins prevents a proteomic analysis. Recently, it could be shown that proteins can be effectively extracted from formalin-fixed and paraffin-embedded samples and that the proteins and phosphorylations are quantitatively preserved compared with fresh frozen tissues (56,61,62).…”
Section: Resultsmentioning
confidence: 99%
“…It has been assumed that the cross-linking of proteins prevents a proteomic analysis. Recently, it could be shown that proteins can be effectively extracted from formalin-fixed and paraffin-embedded samples and that the proteins and phosphorylations are quantitatively preserved compared with fresh frozen tissues (56,61,62).…”
Section: Resultsmentioning
confidence: 99%
“…Most DNA for genetic testing from cancer patients is extracted from formalin-fixed paraffin-embedded tumour biopsies, where the primary intent is to preserve tumour cellular structure for histological examination and diagnosis [5]. However, the formalin fixation process is detrimental to downstream genomic applications, causing issues, such as DNA cross-linking to DNA and proteins, that can stall polymerases and DNA-DNA crosslinks that can inhibit denaturation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The dot blot approach, which is dependent on the detection of a single epitope by an affinity reagent, usually an antibody, is particularly applicable to clinical samples, as it is less sensitive to protein quality than is a sandwich antibody-like approach in which two independent epitopes and the intervening region must be intact for quantitative analysis. Indeed, with a number of caveats, RPPA can be applied to at least a subset of targets from formalin-fixed paraffin-embedded patient samples (33)(34)(35).…”
mentioning
confidence: 99%